2023
DOI: 10.3389/fneur.2022.1017087
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic glioblastoma with glial and epithelioid phenotypes: Clonal evolution and immune selection

Abstract: PurposeEpithelioid glioblastoma is an unusual histologic variant of malignant glioma. The present study investigates both the genomic and transcriptomic determinants that may promote the development of this tumor.MethodsWhole-exome sequencing (WES) and whole-transcriptome sequencing (WTS) were performed on an epithelioid glioblastoma, along with a specific bioinformatic pipeline to generate electronic karyotyping and investigate the tumor immune microenvironment. Microdissected sections containing typical glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There is an urgent need for reliable prognostic models for patients with glioblastoma (GBM), the most common and aggressive primary brain tumor. Dysregulation of the immune microenvironment contributes to the progression of gliomas with TERTp mutations [ 13 , 14 ]. In this work, our analysis of the TCGA-glioma patient cohort exhibiting TERTp mutations showed that patients with high stromal/immune scores had lower survival rates than those with low stromal/immune scores.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for reliable prognostic models for patients with glioblastoma (GBM), the most common and aggressive primary brain tumor. Dysregulation of the immune microenvironment contributes to the progression of gliomas with TERTp mutations [ 13 , 14 ]. In this work, our analysis of the TCGA-glioma patient cohort exhibiting TERTp mutations showed that patients with high stromal/immune scores had lower survival rates than those with low stromal/immune scores.…”
Section: Discussionmentioning
confidence: 99%